Ri chos yon tan kun ʼbyuṅ daṅ lhan thabs : a collection of profound instructions for use during the extended retreat - Yaṅ-dgon-pa Rgyal-mtshan-dpal, 1213-1258 (Dzongsar Jamyang Khyentsey Labrang, 1979)
Instructions on meditation according to the Kargyudpa tradition of Tibetan Buddhism.